Assessment of the Effectiveness of Video-Assisted Teaching on Knowledge Regarding the Management of Post-Hemodialysis Fatigue among Patients Attending Hemodialysis - Pratiksha Munjewar; Ranjana Sharma; Gauri Chandrashekhar Mahakalkar; Archana Dhok; Gaurav Jaiswal (Journal of Pharmacy and Bioallied Sciences)
Background: Chronic kidney disease (CKD) is a global health issue, affecting 13.4% of the population. Many CKD patients progress to end-stage renal disease, necessitating lifelong renal replacement therapy like dialysis. Hemodialysis significantly alters patients’ lifestyles, causing social isolation, work–life changes, financial strain, and family role shifts. These challenges lead to fatigue, pain, depression, and sleep disturbances, severely impacting patients’ quality of life and daily activities. Among these symptoms, fatigue is one of the most common and disruptive. Aim: To assess the effectiveness of video-assisted teaching on knowledge regarding the management of post-hemodialysis fatigue among patients attending hemodialysis. Material and Method: This study was based on a quantitative research approach and one group pretest and post-test research design. This study includes 200 patients attending hemodialysis from Acharya Vinoba Bhave Rural Hospital Wardha with the nonprobability convenience sampling technique. A questionnaire was used to assess the knowledge of the patient. Result: After the educational program, the knowledge score improved significantly. The poor category decreased to 50 participants (25.0%), while the average category dropped to participants (5.0%). The good category increased substantially to 110 participants (55.5%), and 30 participants (15.0%) achieved an excellent level of knowledge. Conclusion: Results suggest that after applying intervention, the knowledge regarding post-hemodialysis fatigue is increased in patients attending hemodialysis.